1999
DOI: 10.1111/j.1875-595x.1999.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Demography and seasonal variation of acute necrotising gingivitis in Nairobi, Kenya

Abstract: The objectives of this study were to determine the frequency of Acute Necrotising Gingivitis (ANG), its sex and age distribution, ethnicity and seasonal variation amongst patients at the Dental Unit of Kenyatta National Hospital (KNH) in Nairobi, Kenya. Cards of patients who were seen in the Dental Unit of KNH in 1992/1993, were scrutinised for positive diagnosis of ANG, age, sex, presenting signs and symptoms and treatment that was given. Of the 53,572 patients who were treated, (0.15 per cent) had ANG. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Generally, studies in African populations report a higher prevalence of necrotizing periodontal diseases in children than in populations older than 10 years of age (35, 73, 84, 87). Kaimenyi (53) examined records of about 53 000 patients attending a dental hospital in Nairobi, Kenya during 1992–1993, and found that 0.15% of these had necrotizing ulcerative gingivitis, and that 58.5% of all positively diagnosed cases were younger than 11 years of age.…”
Section: Necrotizing Periodontal Diseasesmentioning
confidence: 99%
“…Generally, studies in African populations report a higher prevalence of necrotizing periodontal diseases in children than in populations older than 10 years of age (35, 73, 84, 87). Kaimenyi (53) examined records of about 53 000 patients attending a dental hospital in Nairobi, Kenya during 1992–1993, and found that 0.15% of these had necrotizing ulcerative gingivitis, and that 58.5% of all positively diagnosed cases were younger than 11 years of age.…”
Section: Necrotizing Periodontal Diseasesmentioning
confidence: 99%
“…Emslie (57) found a single case of acute ulcerative gingivitis among 54 children under the age of 10 years in Sudan. Kaimenyi (106) found 82 cases of acute necrotizing gingivitis among 53 572 patients attending a hospital dental clinic in Kenya. Thirty of these cases were seen in children aged 2–6 years, 16 cases were seen among 7–10‐year‐old children, and 22 cases were observed among 21–30‐year‐old‐persons.…”
Section: Special Forms Of Periodontal Diseases Among African Populationsmentioning
confidence: 99%
“…Thirty of these cases were seen in children aged 2–6 years, 16 cases were seen among 7–10‐year‐old children, and 22 cases were observed among 21–30‐year‐old‐persons. Although the prevalence among 0–10‐year‐old children was low (∼0.15%), the observation of a substantial number of cases of necrotizing gingivitis among the 21–30‐year olds was remarkable, and possibly attributable to ‘the upsurge of AIDS’ (106).…”
Section: Special Forms Of Periodontal Diseases Among African Populationsmentioning
confidence: 99%
“…Despite the continued and widespread interest in the manifestations of necrotizing ulcerative gingivitis (NUG) relatively little is known about the prevalence, distribution and predictors for this condition. Many prevalence estimates originate in studies based on persons attending various dental health facilities (1–13), which means that the estimates could easily be biased due to the self‐selection involved in such study designs. Similarly, most information on the risk factors for NUG originate in case‐series [for reviews see (14–18)].…”
mentioning
confidence: 99%